2009
DOI: 10.1108/14630010910940543
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of activity, space and cost variables in office workstation sharing

Abstract: Purpose -The growth in flexible working by employees in many office-based organisations means that workstation sharing at the employer's premises is increasingly attractive. However, because of peaks and troughs in demand it is difficult to decide how many workstations should be provided. The purpose of this paper is to investigate the cost-effectiveness of alternative workstation sharing strategies. Design/methodology/approach -The study used an agent-based simulation model with two input variables: the emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…Correlations between work ergonomics and employee productivity. This finding is confirmed in previous studies by Roelofsen [3], Haynes [8], and Fawcett and Rigby [23] which suggested that there exists a positive and significant correlation between general design and workplace décor and employee productivity. Also, De Been and Beijer [24] posited that there is a high positive impact of workplace type on employee productivity.…”
Section: Impact Of Work Ergonomics On the Productivity Of Pfc Employeessupporting
confidence: 81%
See 1 more Smart Citation
“…Correlations between work ergonomics and employee productivity. This finding is confirmed in previous studies by Roelofsen [3], Haynes [8], and Fawcett and Rigby [23] which suggested that there exists a positive and significant correlation between general design and workplace décor and employee productivity. Also, De Been and Beijer [24] posited that there is a high positive impact of workplace type on employee productivity.…”
Section: Impact Of Work Ergonomics On the Productivity Of Pfc Employeessupporting
confidence: 81%
“…This implies that whenever the organization enhances its spatial arrangement and furnishing, it results in improving its employee productivity. Similar studies by Becker [25], Fawcett and Rigby [23], and Saleem et al [10] have shown a significant positive association between spatial arrangement and furnishing, and employee productivity.…”
Section: Impact Of Work Ergonomics On the Productivity Of Pfc Employeessupporting
confidence: 66%
“…Examples of these solutions include: touchdown areas that allow staff to access information quickly; bookable offi ces; and group collaborative workspaces such as board rooms equipped with technology to provide teleconferencing capabilities; and hot-desking ( Pitt and Bennett, 2008 ). Hot-desking refers to the approach of compelling employees to share workstations through providing fewer workstations than employees to achieve the objectives of attaining higher workstation utilization and reducing the costs of providing workstations ( Fawcett and Rigby, 2009 ).…”
Section: Operations and Activities Of The Organizationmentioning
confidence: 99%
“…Therefore, organizations have started to devise approaches to minimize this cost through requiring employee to share workstations ( Fawcett and Rigby, 2009 ). However, attempts to achieve cost-savings in this trait might result in decreasing the employees ' productivity due to frequent distractions and loss of concentration ( Erlich and Bichard, 2008 ).…”
Section: Cost Per Worktationmentioning
confidence: 99%
“…In other words, a larger margin of available workplaces is needed to accommodate bigger fluctuations in the demand for space. In another article he describes a simulation model that aims to find out whether the option of sharing places is suited for an organisation (Fawcett & Rigby, 2009). By using an agent based simulation model that takes different elements into account and simulates the demand for places in different 'runs', it uses probability to visualise demand for workplaces at different times.…”
Section: Introductionmentioning
confidence: 99%